2019
DOI: 10.1039/c9mh00195f
|View full text |Cite
|
Sign up to set email alerts
|

Phenanthro[9,10-d]triazole and imidazole derivatives: high triplet energy host materials for blue phosphorescent organic light emitting devices

Abstract: A class of wide bandgap host materials is introduced as an alternative to carbazole-based hosts to enhance the efficiency and transport properties of organic light emitting diodes (OLEDs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 40 publications
2
37
0
Order By: Relevance
“…This effect of film composition on phosphorescence has been observed previously by others for CBP and its twisted analogue 4,4’‐bis(9‐carbazolyl)‐2,2’‐dimethylbiphenyl CDBP , [27, 54, 73] as well as several other materials [74, 75] . However, despite the logical implications for triplet energies and how these determine host/guest compatibility, it is not commonplace to report neat film phosphorescence of new OLED host materials.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…This effect of film composition on phosphorescence has been observed previously by others for CBP and its twisted analogue 4,4’‐bis(9‐carbazolyl)‐2,2’‐dimethylbiphenyl CDBP , [27, 54, 73] as well as several other materials [74, 75] . However, despite the logical implications for triplet energies and how these determine host/guest compatibility, it is not commonplace to report neat film phosphorescence of new OLED host materials.…”
Section: Resultssupporting
confidence: 58%
“…Instead, low temperature solution measurements currently dominate the literature in reports of this kind [69, 76–87] . A recent study by Forrest and Thompson [73] has demonstrated that such solution measurements do not give appropriate triplet energies for the design of OLEDs, while the results here show that phosphorescence in dilute polymer films is also not suitable in this regard. We therefore suggest that neat film phosphorescence measurements should become the accepted standard for reporting E T of novel OLED host materials.…”
Section: Resultsmentioning
confidence: 74%
“…[7] The OLED performance parameters are given in Table 4 and plots of device efficiencies versus luminance are given in the Supporting Information. In these devices, fac-Ir(tpz) 3 was used as a blue dopant in an emissive layer comprised of mCBP mCBP/8% Firpic [7] 3. The FIrpic EL spectrum in mCBP consists of two roughly equal intensity peaks.…”
Section: Electroluminescence Propertiesmentioning
confidence: 99%
“…[2] Cyclometalated iridium(III) complexes have emerged as one of the most promising triplet emitters because of their versatile color tunability, chemical stability, good thermal properties, and high photoluminescent quantum yields (Φ PL ). [3][4][5][6][7] These phosphors often involve an octahedral Ir 3+ ion with bidentate ligands, C^N:, comprised of a covalently bonded aryl moiety and a datively bonded nitrogen group, such as pyridyl, to give a tris-cyclometalated complex, Ir(C^N:) 3 . While efficient OLEDs using red and green Ir-based phosphorescent emitters are commercially viable, [8][9][10] the stability of OLEDs using blue-emitting transition metal containing complexes are presently insufficient for practical applications.…”
mentioning
confidence: 99%
“…Moreover, the three-component cyclocondensation reaction of tris-aldehyde 3 with 9,10-phenanthrenequinone 25 and ammonium acetate afforded the corresponding tris(1H-phenanthro[9,10-d]imidazole) 26 as a new building block for blue light-emitting materials (Scheme 9). 74 Compound 24 was conrmed by the absence of characteristic absorption bands or signals for CHO, NH 2, or SH in its IR or 1 H NMR spectra. The structure of the tris(imidazole) 26 was dened on the basis of spectral data.…”
Section: Resultsmentioning
confidence: 99%